Preparation, Structure, and enhanced thermoelectric properties of Sm-doped BiCuSeO oxyselenide - Bo Feng; Xingxing Jiang; Zhao Pan; Lei Hu; Xiaoming Hu; Peihai Liu; Yang Ren; Guangqiang Li; Yawei Li; Xi’an Fan (Materials & Design, 2020)
The layered oxyselenide BiCuSeO was recently discovered to be a promising high thermoelectric material due to its intrinsically low thermal conductivity. However, the rather high electrical resistivity of undoped BiCuSeO may preclude its potential thermoelectric applications. Herein, we achieved enhanced thermoelectric performance in rare-earth Sm-doped BiCuSeO by the band structure engineering. The replacement of Bi3+ by Sm3+ leads to the improvement of electrical conductivity, from 34 S cm−1 for pristine BiCuSeO to 79 S cm−1 for that of Bi0.94Sm0.06CuSeO at 873 K. Coupled with the large Seebeck coefficient (251 μVK−1) and relatively low thermal conductivity (0.58 Wm−1K−1), the figure of merit ZT is significantly increased from 0.49 for pristine BiCuSeO to 0.74 for Bi0.94Sm0.06CuSeO at 873 K. According to the first-principles calculation, the enhanced thermoelectric properties was ascribed to the decreased band gap by the substitution of Sm. Upon 10%Sm substitution, the band gap of BiCuSeO decreases from 0.50 eV to 0.34 eV, which promotes the density of states near the Fermi level. The present study suggests that rare-earth element can be effective in modifying the band structure of BiCuSeO and thus improving its electronic transport properties. Keywords: Sm-doping, Thermoelectric properties, Band structure, First-principles calculation